Cooked yields, cooked color, tenderness, and sensory traits of beef roasts differing in connective tissue content cooked in an oven with steam generation versus a commercial convection oven to different endpoint temperatures - Bowers, Lindsay Jeanine (Kansas State University, 2011)
The CVap steam generation oven was compared to a Blodgett forced-air, convection oven to examine effects of cooking method on yields, cooked color, tenderness, and sensory traits of beef Longissimus lumborum (LL), Deep pectoralis (DP), and Biceps femoris (BF) muscles cooked to three endpoint temperatures (65.6, 71.1, and 76.7°C). For each cooking treatment, four roasts were cooked in the CVap oven for a pre-determined, average amount of time, and two roasts were cooked in the Blodgett oven until they reached desired internal endpoint temperature. Cooking yields were higher (P ≤ 0.05) for BF and LL roasts cooked in the CVap. Slice shear force (SSF) for BF roasts cooked in the CVap were lower (P ≤ 0.05), whereas, SSF values for DP roasts cooked in the Blodgett were lower (P ≤ 0.05). No oven difference (P > 0.05) was found for LL roasts. Sensory tenderness scores for BF roasts cooked in the CVap were slightly higher (P ≤ 0.05) than roasts cooked in the Blodgett. Sensory scores for LL roasts cooked in the CVap were slightly higher but were also drier (both P ≤ 0.05). The CVap oven offers tenderization and cooking yield advantages for certain muscles.
Keywords: Beef; Cooking method; Tenderness; Yield; Animal Sciences (0475)